2014
DOI: 10.1038/srep04324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BZG-4000, a novel multi-targeted kinase inhibitor with potent anticancer activity, on a hepatocellular carcinoma xenograft model

Abstract: The present study was to synthesize a novel multi-targeted kinase inhibitor and evaluated its anticancer effects on a hepatocellular carcinoma xenograft model. In our study, in vivo efficacy was determined in nude mice bearing HuH7 human HCC xenografts. The mice were randomly divided into the following five groups with the use of a randomization chart (n = 8 in each group): high-dose BZG-4000 group, medium-dose BZG-4000 group, low-dose BZG-4000 group, sorafenib group, and model group. Tumor size measurements i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Available cancer therapies such as chemotherapy, liver transplantation, surgical resection, radiofrequency ablation, immunotherapy, and hormone therapy have different response rates and efficacies due to the vast heterogeneity of HCC [26,27]. Sorafenib is an approved molecularly targeted therapy that is administered for treatment of patients with advanced HCC through its antiproliferative, antiangiogenic, and proapoptotic functions.…”
Section: Discussionmentioning
confidence: 99%
“…Available cancer therapies such as chemotherapy, liver transplantation, surgical resection, radiofrequency ablation, immunotherapy, and hormone therapy have different response rates and efficacies due to the vast heterogeneity of HCC [26,27]. Sorafenib is an approved molecularly targeted therapy that is administered for treatment of patients with advanced HCC through its antiproliferative, antiangiogenic, and proapoptotic functions.…”
Section: Discussionmentioning
confidence: 99%
“…BZG also inhibited in vitro proliferation of a panel of human cancer cells [ 7 ]. Moreover, our previous research indicated that BZG significantly inhibited Huh-7 cell derived tumor xenografts in Balb/c nude mice [ 7 , 8 ]. Studies showed relatively high concentrations of BZG in the liver and kidney providing a pharmacokinetic (PK) basis for their effective use in hepatic and renal carcinomas [ 9 ].…”
Section: Introductionmentioning
confidence: 99%